Deep Learning-Based Academic Writing Instruction in Higher Education: Enhancing Students’ Critical and Reflective Writing Skills - Abdul Rahman R. (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
The development of academic writing competence has become an essential objective in higher education, particularly in the context of 21st-century learning. However, many university students still experience difficulties in developing critical arguments, organizing academic ideas, and producing reflective academic texts. This study aims to explore the implementation of deep learning-based instruction in academic writing courses and its contribution to enhancing students’ critical and reflective writing skills. The study employed a qualitative descriptive approach involving undergraduate students enrolled in academic writing classes. Data were collected through classroom observations, semi-structured interviews, and documentation analysis. The findings revealed that deep learning-based instruction encouraged students to engage actively in the writing process through critical inquiry, collaborative discussion, reflective learning, and contextual problem-solving. Students demonstrated improvements in idea organization, argument development, academic engagement, and reflective thinking. Furthermore, the integration of deep learning principles in academic writing instruction fostered meaningful learning experiences and strengthened students’ confidence in expressing academic arguments. The study concludes that deep learning-based instruction provides an effective pedagogical approach for improving academic writing competence in higher education. The findings imply that academic writing instruction should move beyond product-oriented practices toward reflective, student-centered, and inquiry-based learning environments.